2003
DOI: 10.1523/jneurosci.23-12-05283.2003
|View full text |Cite
|
Sign up to set email alerts
|

Concerted GABAergic Actions ofAplysiaFeeding Interneurons in Motor Program Specification

Abstract: GABAergic inhibitory interneurons regulate the activity of diverse types of neural networks, but the specific roles of these interneurons in motor control are poorly understood. In the Aplysia feeding motor network, three interneurons, cerebral-buccal interneuron-3 (CBI-3) and buccal interneurons B40 and B34, are GABA-immunoreactive and evoke fast IPSPs in their postsynaptic followers. Using a combination of pharmacological experiments with GABA antagonists, agonists, and uptake inhibitors, we found that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 60 publications
(95 reference statements)
4
91
0
1
Order By: Relevance
“…Assays of monosynapticity were conducted in high-divalent saline containing (in mM): 312 NaCl, 10 KCl, 132 MgCl 2 , 33 CaCl 2 , and 10 HEPES, pH 7.6, a solution that elevates spike thresholds and thus curtails polysynaptic activation (Cohen et al, 1978;Trudeau and Castellucci, 1992). Neurons were identified on the basis of location, size, and electrophysiological and morphological characteristics (Rosen et al, 1991;Hurwitz et al, 1997;Jing and Weiss, 2001;Jing et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assays of monosynapticity were conducted in high-divalent saline containing (in mM): 312 NaCl, 10 KCl, 132 MgCl 2 , 33 CaCl 2 , and 10 HEPES, pH 7.6, a solution that elevates spike thresholds and thus curtails polysynaptic activation (Cohen et al, 1978;Trudeau and Castellucci, 1992). Neurons were identified on the basis of location, size, and electrophysiological and morphological characteristics (Rosen et al, 1991;Hurwitz et al, 1997;Jing and Weiss, 2001;Jing et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work on biting and rejection-like motor programs Weiss, 2001, 2002;Jing et al, 2003) suggested that the Aplysia feeding network has a modular organization. Here, we characterize swallowing and rejection-like motor programs that are elicited by a higher-order interneuron, cerebral-buccal interneuron-4 (CBI-4), and determine whether modules are behavior specific or independent.…”
Section: Introductionmentioning
confidence: 98%
“…Control of I2 duration and intensity may be attributable to actions of GABAergic interneurons (Jing et al, 2003). It is clear that the combination of shifting coalitions of muscles, and a reorganizing neural architecture, are critical for multifunctionality.…”
Section: Multifunctionality and Muscular Coalitionsmentioning
confidence: 99%
“…Next, we sought to determine whether CBI-11 acts on buccal CPG elements that are important for the expression of different types of motor programs. We first recorded from B40 Jing et al, 2003), an interneuron that is critical for the expression of ingestive programs, by promoting more B8 activity during retraction and less B8 activity during protraction. We found that CBI-11 elicited monosynaptic EPSPs on B40, which persisted in high-divalent saline (Fig.…”
Section: Program Specification By Cbi-11 and Its Effects On Cbi-2-drimentioning
confidence: 99%
“…However, more recent work showed that pattern-generating networks activated by command neurons are often multifunctional; that is, they generate multiple types of motor programs (Nusbaum and Beenhakker, 2002;Jing and Weiss, 2005;Marder and Bucher, 2007;Briggman and Kristan, 2008;Benjamin, 2012). Therefore, to initiate behavior, it does not suffice to simply trigger activity in the motor network-the type of program induced must also be specified.…”
Section: Introductionmentioning
confidence: 99%